'I am actually doing something to keep well. That feels really good': Experiences of exercise within hospice care. (3rd July 2016) - Turner, Karen; Tookman, Adrian; Bristowe, Katherine; Maddocks, Matthew
Abstract : Background: Patients with advanced cancer frequently experience functional impairment and reduced quality of life. Therapeutic exercise can provide benefit and be made accessible through the use of tailored programmes. Most studies examining exercise programmes for people with advanced cancer have used quantitative outcome measures and focussed on objective physical function, therefore offer a limited perspective on the experience of exercise participation. Methods: This qualitative study explored patients' experiences of an exercise programme within a palliative care setting. The interviews focussed on the perceived impact on all aspects of quality of life. Results: Nine people with advanced cancer, attending a hospice-based exercise programme, completed a one-to-one interview with a senior physiotherapist to explore the physical, emotional, and social impacts of their participation. Interviews were audiotaped, transcribed verbatim and analysed using interpretive phenomenological analysis. Patients reported an awareness of the positive physical, psychological, and social consequences of exercising. Their experiences reflected on all dimensions of quality of life, the impact of others and the sense of meaning gained through participation in exercise. Conclusion: Our findings highlight that exercise in palliative care should not be viewed solely a physical intervention, but one that has potential to enhance many aspects of patients' quality of life.